Chemical properties of heat-treated rubberwood / Rafeadah R. ...[et al.] - R., Rafeadah; S., Rahim; S., Slamah; H., Shaharuddin (2006)
The usage of chemical preservative lead to environmental concerns regarding the process of treating, the loss of chemicals in service and the disposal of the treated wood at the end of its service life. Thus, heat treatment using steam is an alternative method to increase the durability of wood against fungus and termite, reduce the hygroscopicity and improve dimensional stability. The present study is undertaken to determine the effect of pressure and treatment schedule on chemical properties of rubberwood. The heat treatments were done at pressures, 30, 60, 90 and 120 psi .1nd durations, 30, 60, 90 and 120 min. The chemical analysis of the heat-treated rubberwood for all treatments showed there were variations on the percentage of holocellulose, a-cellulose, lignin and extractives content compared with the untreated rubberwood. The percentages of holocellulose and lignin decreased as the pressures and durations increased and they were lower compared with the untreated sample. The 120 psi-treated samples gave the highest percentage of ethanol-toluene, extractives compared with the other treated and untreated samples.